Controlador de temperatura para célula de medição de propriedades de líquidos por ultrassom - Lugão, João Ricardo Lhullier [UNESP] (2016)
Temperature control systems are required in several industry and scientific research areas. This work proposes a liquid temperature control system applied to an ultrasonic mea- surement cell for liquids. The control system requires a maximum steady state deviation of 0,01 ◦ C. Thermoelectric coolers (TEC) work as thermal actuators with H bridge power circuits to pump heat to or from the object of interest. Resistive temperature detectors (RTD) are used in this work, which are linear and widely used in the industry as temperature measurement reference. A proportional, integral and derivative (PID) digital controller is tuned using relay feedback identification with direct tuning methods, such as Ziegler-Nichols’. To improve the results a fine tuning is implemented from the parameters estimated by the direct methods. A PID controller capable of achieving the 0,01◦ C maximum variation goal is implemented. With this low steady-state oscilation it is possible to measure phase velocity of ultrassound waves in distilled water with maximum variation of 0,05 m/s around the mean value.